1658 The new ilo list of occupational diseases: guidance notes on diagnostic criteria for occupational diseases included in the ilo list. (24th April 2018) - Colosio, Claudio; Niu, Shengli; Laan, Gert van der
Abstract : Aim of special session: In 2010 the new ILO list of occupational diseases was adopted, which was established for prevention, diagnosis and compensation of occupational diseases. After the adoption, an international experts group was set up to help the International Labour Office in the preparation of guidance notes on the diagnostic criteria for the occupational diseases included in the ILO list. This group has kept a lose contact with the WHO working group on occupational diseases in ICD11. The notes cover all the groups of diseases included in the ILO list (more than 100 monographs in total. The notes also include a part on prevention in relation to each disease or diseases' groups. This minisymposium is organised to provide background information on the major issues in the process of the preparation for the Guidance Notes, the role and application of these notes, the linkage between the ILO list and the WHO ICD, the national practice and expertise on the recognition of OD. Interaction between the invited presenters and audiences is included on the arrangement of this minisymposium. During the preparation of the workshop. Prof. Tar Chin Aw suddenly passed away, Prof. Colosio will deliver a presentation also on the name of the colleague who participated in the preparation of the event and was supposed to provide a presentation. Shengli Niu 2, Anil Adisesh 4, Claudio Colosio 1, Jorma Rantanen 5, Swen Malte John 6, Igor Bukhtiyarov 7, Zhang Min 8, Linda Forst 9, Annet F. Lenderink 10, Ivan Ivanov 11 1 Department of Health Sciences of the University of Milan and International Centre for Rural Health of the S. Paolo Hospital, Italy 2 International Labour Organisation, Geneva, Switzerland 3 Foundation Learning and Developing Occupational Health, Speelkamp 28, 3831 PE Leusden, The Netherlands Finnish Institute of Occupational Health, Centre of Expertise for Development of Work and Organisations, Topeliuksenkatu 41 a A, 00250 Helsinki, Finland Solvent Team Amsterdam, Netherlands Centre for Occupational Diseases, Coronel Institute of Occupational Health, Academic Medical Centre, University of Amsterdam, Meibergdreef 9, 1105 AZ Amsterdam, The Netherlands 4 Dalhousie University, Halifax, Canada 5 University of Helsinki, Department of Public Health/Occupational Health, Helsinki, Finland 6 Dept. Dermatology, Environmental Medicine, Health Theory, University of Osnabrueck, Osnabrueck, Germany 7 FSBSI 'Izmerov Research Institute of Occupational Health', Moscow, Russia 8 Chinese Academy of Medical Sciences (CAMS)/Peking Union Medical College (PUMC), Beijing, China 9 University of Illinois at Chicago School of Public Health, Illinois, US 10 Netherlands Centre for Occupational Diseases, Coronel Institute on Work and Health, AMC/University of Amsterdam, Amsterdam, Netherlands